GILLES'IO DELEUZE'O IR FELIXO GUATTARI MIKRO-POLITIKA ŠIUOLAIKINĖS FILOSOFIJOS KONTEKSTE. - Žukauskaitė, Audronė (Problems / Problemos, 2009)
The article discusses Deleuze and Guattari's concept of micropolitics in relation with the notions of minor literature and becoming-minoritarian. Tthe concept of minor literature appears in Deleuze and Guattari's Kafka: Toward a Minor Literature and is defined by three characteristics: 1) the deterritorialization of language; 2) the connection of the individual to a political immediacy; 3) the collective assemblage of enunciation. The notion of minor literature is closely related with the notion of becoming-minoritarian developed in A Thousand Plateaus. Deleuze and Guattari claim that becoming-minoritarian is the universal figure of consciousness. In this sense, any kind of becoming is a revolutionary act, because it changes the political constellation of power and enables the repressed to reach an autonomous condition. The concept of becoming-minoritarian is introduced to the contemporary political context through the notion of minor politics, discussed by Nicholas Thoburn. Minor politics is seen not as a fetishization of marginal identity but rather as a possibility to legitimize the existence of those who lack any social identity. In this sense, the notions of becoming-minoritarian and minor politics are contrasted with Alain Badiou's claim to universality: the question is raised as to whether becoming-minoritarian should necessarily end in autonomy, as Deleuze and Guattari argue, or, by contrast, whether it should seek to universalize the minor and in this way raise the claim for universal justice.